2022
DOI: 10.1177/00027642221118268
|View full text |Cite
|
Sign up to set email alerts
|

The 21st Century Globetrotters’ Fans: The Case of Israeli Transnational Football Supporters’ Communities Before and During the Pandemic

Abstract: In the modern era of commercialized, mediated, and global football, there is a decline in the importance of the local aspect of sports fandom. Nowadays, through television broadcasts, the Internet, and especially social networks, a fan continuously follows elite football clubs from around the world, which provide an alternative to local clubs. This has created a growing trend of football fan communities known as “transnational fans”—fans of sports clubs from other countries. Contrary to traditional definitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Traditionally, hardcore fans were measured by their attendance in the stands, and those who followed the team on home and away games were considered the most loyal (12). However, given current tendencies in the globalization of sports, particularly football (13), some fans choose alternative ways of demonstrating their dedication (14). While some fans continue to support their team in the traditional way of attending matches, others focus on the consumer aspect of fandom (15).…”
Section: Trivial Knowledge As An Indicator Of Fandom's Qualitymentioning
confidence: 99%
“…Traditionally, hardcore fans were measured by their attendance in the stands, and those who followed the team on home and away games were considered the most loyal (12). However, given current tendencies in the globalization of sports, particularly football (13), some fans choose alternative ways of demonstrating their dedication (14). While some fans continue to support their team in the traditional way of attending matches, others focus on the consumer aspect of fandom (15).…”
Section: Trivial Knowledge As An Indicator Of Fandom's Qualitymentioning
confidence: 99%
“…Sepak bola bukan hanya perihal sebelas orang yang bermain di lapangan, akan tetapi para suporter yang berdiri di tribun juga termasuk pemain yang berada di dalamnya (Kennedy & Kennedy, 2010). Bagi mereka bukan pula sekedar menyaksikan, akan tetapi memberikan komentar, seruan suporter kepada tim kesayangan dan seruan intimidasi pada tim lawan pun sebagai implusif perlu mewujudkan tindakan lanjutan (Levental et al, 2023). Di Indonesia apalagi di dunia, sepak bola dan suporter sepak bola adalah kesatuan yang tidak dapat dipecahkan serta sama-sama berkaitan (Malfaid, 2013).…”
Section: Pendahuluanunclassified
“…Various forms of fandom have been identified and categorized by researchers, predicated on the degree of identification fans exhibit toward their team ( Giulianotti, 2002 ; Billings et al, 2018 ; Onwumechili, 2018 ; Van Driel et al, 2019 ; Levental et al, 2022 ). Wann et al (2001) suggest a framework that differentiates highly identified fans from mere sports spectators.…”
Section: Introductionmentioning
confidence: 99%